The Mitigation of Wildlife - Communities Conflict In Gunung Leuser National Park (Case Study of Timbang Lawan and Timbang Jaya Village, Bahorok Sub-District, Langkat Regency) - Wilda Hasanah Harahap; Pindi Patana; Yunus Afifuddin (Peronema Forestry Science Journal, 2013)
Research on "The mitigation of wildlife-communities conflict in Gunung Leuser National Park" was conducted in July until August 2012. This research aimed to identify any factors caused wildlife that often enter into community plantations, to calculate the economic losses due to conflicts with wildlife and to analysis of wildlife handling by the communities. The method used in this research are observation, filling questionnaires and interviews to people directly. The results of this research are the factors that cause conflicts between wildlife with communities which the habitat destruction due to forest encroachment and the level of wildlife preference for the type of plant. The treatment used by communities to overcome the damage and economic loss are making sounds like fireworks, cheers by the owner of the land, shoot the animals with a pellet gun, maintained, done by making a trap or snare, made ​​a bonfire and leave it. Average economic losses of crops in the Timbang Lawan and Timbang Jaya villages are Rp. 104.090,00/person/month, while average annual economic losses of crops in Timbang Lawan and Timbang Jaya villages are Rp.25.465,00/person/month. Keywords: Conflict of wildlife, Mitigation, Gunung Leuser National Park.